The effects of crude oil boiling treatment on physical properties of Bambusa vulgaris var. Striata (Buluh Gading) - Kamal, Izran; Wahab, Razak; Ashaari, Zaidon; Abood, Faizah; Ahmad Razi, Norhisham (Universiti Putra Malaysia Press, 2012)
Bamboo is a material formed from organic components such as cellulose, hemicelluloses and lignin. It is often attacked by biodegradation agents due to the presence of the organic components which affect the physical properties and durability of the bamboo, hence limiting its utilization as an input for production of value-added products. Preservation treatment for lignocellulosic material is not an exception. Boiling treatment was found to be one of the eco-friendly methods to preserve the material. A research was undertaken to study the effects of crude oil boiling treatment on the physical properties and durability of Bambusa vulgaris var. Striata (Buluh Gading) against biodegradation agents. Bamboo strips were boil treated in palm oil at 160-2000C for 10 minutes. The untreated and treated strips were tested using physical tests such as relative density, moisture content, swelling and shrinkage. The durability of the strips was also tested using weathering test, where they were exposed to the surrounding for 3 months. The results showed that the boiling treatments improved the dimensional stability of the bamboo and its durability against fungi and boring insects. Meanwhile, the treatments at different temperatures significantly affected the relative density, moisture content, durability, swelling and shrinkage of the bamboo. The moisture content, swelling and shrinkage dropped with regards to the increase in the treatment temperature. The reductions were 18.6% – 2.38%, 16.28% -7.51%, and 20.72% - 10.94, respectively. The relative density increased to 0.89% when the treatment temperature increased to 1600C, but it decreased from 0.89 to 0.74% as the temperature was increased to 2000C. The durability was assessed in term of percentage of weight loss (%). A smaller percentage of the weight loss indicates a better durability. Thus, the treatments were effective to reduce the percentage of weight loss for the above-ground and in ground graveyard tests. The reductions were found to range from 28.14% - 9.92% and 28.14 – 3.39%, respectively. This study has indicated that bamboo becomes less hygroscopic and more durable when it is exposed to higher temperatures.